Prevalence of dyslipidemia and associated risk factors among adults aged ≥35 years in northern China: a cross-sectional study - Yunfeng Xi; Liwei Niu; Ning Cao; Han Bao; Xiaoqian Xu; Hao Zhu; Tao Yan; Nan Zhang; Liying Qiao; Ke Han; Gai Hang; Wenrui Wang; et al. (BMC, 2020)
Abstract Background Cardiovascular disease (CVD) prevalence has increased continuously over the last 30 years in China. Dyslipidemia is an important modifiable risk factor in CVD. We aimed to collect current data on the prevalence of dyslipidemia in northern China and explore potential influencing factors. Methods In this cross-sectional study, we selected a representative sample of 65,128 participants aged ≥35 years in Inner Mongolia during 2015-2017. All participants completed a questionnaire and were examined for risk factors. Dyslipidemia was defined according to 2016 Chinese guidelines for adults. The associated factors for dyslipidemia were estimated by multivariate logistic regression analysis. Results The age-standardized prevalence of dyslipidemia was 31.2% overall, with 4.3, 2.4, 14.7, and 17.4% for high total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), and low high-density lipoprotein cholesterol (HDL-C), respectively. The dyslipidemia prevalence was significantly higher in men than women (37.9% vs. 27.5%, P < 0.001), but postmenopausal women had a higher prevalence of dyslipidemia components (except low HDL-C). Compared with Han participants, Mongol participants had a lower prevalence of dyslipidemia (29.1% vs. 31.4%, P < 0.001). Male sex, living in urban areas, Han ethnicity, smoking, obesity, central obesity, hypertension, and diabetes were all positively correlated with dyslipidemia; alcohol consumption was linked to lower risk of dyslipidemia. Conclusions Our study revealed that dyslipidemia is a health problem in northern China. Greater efforts to prevent and manage dyslipidemia, especially in men under age 55 years, postmenopausal women, and people with unhealthy lifestyles or chronic diseases.